Utopian Geographies and the Early English Novel - Pearl, Jason H. (Book collections on Project MUSE., 2014)
"This book considers how writers of the late seventeenth and early eighteenth centuries engaged critically and creatively with the idea of utopia--in particular the idea of utopia as a geographic location--and how questions about world geography and utopian possibility drove many of the formal innovations of the early English novel. Works examined include Margaret Cavendish's Blazing World, Aphra Behn's Oroonoko, Defoe's Robinson Crusoe and Captain Singleton, and Swift's Gulliver's Travels"--